Why Should We Become Posthuman? The Beneficence Argument Questioned. Issue 2 (16th March 2019) - Pablo Vaccari, Andrés
Abstract: Why should we become posthuman? There is only one morally compelling answer to this question: because posthumanity will be a more beneficial state, better than present humanity. This is the Posthuman Beneficence Argument (PBA), the centerpiece of the liberal transhumanist defense of "directed evolution." In this article, I examine PBA and find it deficient on a number of lethal counts. My argument focuses on the writings of transhumanist philosopher Nick Bostrom, who has developed the most articulate defense of PBA and disclosed its metaethical framework. I begin by locating PBA in the context of wider transhumanist claims for the desirability of posthumanity. I identify two crucial components: (1) a model of deliberative rationality, requiring reasons to endorse claims; and (2) the reasons themselves (i.e., the greater beneficence that posthumanity represents). I examine these two conditions, in turn, specifying the claims that they ask us to accept. Following Bostrom, I argue that there is a need for a foundationalist approach that assures us of some universality in the process of valuation. This is required to appropriately ground the moral continuity and appeal to universality that PBA demands. I examine the reasons why this approach ultimately fails, leaving posthumanity as an unintelligible concept with no moral force. I conclude by identifying (and endorsing) a more mature approach to the debate on human enhancement, one that forfeits the grandiose but baseless claims too often found in transhumanist defenses of directed evolution. In short, posthumanity may be a good science fiction trope, but it has no normative force in the moral philosophy of human enhancement.